2021
DOI: 10.3389/fpsyt.2021.763367
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Video Feedback Within a Community Based Naturalistic Developmental Behavioral Intervention Program for Toddlers With ASD: Pilot Study

Abstract: Video feedback (VF) is an intervention delivery technique that complements naturalistic developmental behavioral interventions (NDBI) and parent-mediated interventions (PMI) by using caregiver-child interaction videos reviewed with a clinician to facilitate behavioral change in caregivers. Although VF has been implemented in PMI with young children with ASD, examinations of feasibility and acceptability, as well as the potential effectiveness of VF in community settings, have been limited. In this pilot random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Our findings are also consistent with previous evidence reporting that video feedback is an effective and well-accepted strategy to coach parents of young children with autism in various intervention models [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also consistent with previous evidence reporting that video feedback is an effective and well-accepted strategy to coach parents of young children with autism in various intervention models [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the video-feedback modality, conversely, the interactions between the parent and the child are videotaped asynchronously; the videos are sent to the therapist before the video-conferencing session and discussed during the online session [ 23 , 24 , 25 , 26 , 27 ]. The video-feedback review moment represents an opportunity for the parent to observe themselves “from the outside” and to reflect on their behaviors and the child’s responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, although several studies have reported good levels of acceptability related to intervention delivered via telehealth (Pickard et al, 2016 ; Sengupta et al, 2021a ), in virtual CST caregiver participation was lower and contents were overall found to be less acceptable by caregivers, as well as more complex to deliver by facilitators. This may be due to the fact that the virtual CST group disproportionately included parents of non-Italian nationality, who reported indeed that their difficulties with understanding the language were worsened by technological issues, as previously found (Klein et al, 2021 ; Lee et al, 2015 ). In our study we report lower ratings of caregiver participation in virtual CST compared to in-person CST, mirrored by qualitative findings of emotional distance and impotence perceived by facilitators and caregiver difficulties in creating meaningful relationships in virtual CST.…”
Section: Discussionmentioning
confidence: 55%
“…Technical issues and cumbersome processes to share the videorecording also affected the video-feedback during the virtual home visits, resulting in lack of delivery in a third of opportunities. When video feedback was feasibly delivered, caregivers found it highly useful to have reviewed themselves and their child, as previously reported (Klein et al, 2021 ), but reported that the presence of the camera and the interventionist’s voice during the direct coaching were interfering with the child’s spontaneous behaviour, thus affecting its representativeness. Communicating via Bluetooth headphones or the videoconferencing chat to guide the caregiver and placing the device out of the child’s sight were put forward as possible strategies by facilitators, as suggested by others (Lerman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation